DESCRIPTION OF DIET COMPLIANCE IN HEMODIALYSIS PATIENTS IN GUNTUR HOSPITAL GARUT - Nugraha, Bambang Aditya; Sulastini, Sulastini (Karsa Husada Health Institute Garut, 2023)
Chronic kidney disease is a condition when kidney function decreases to the point where the kidneys are unable to filter the body's metabolic waste and maintain the balance of electrolyte fluids such as sodium and potassium. One of the problems that is often found in chronic kidney failure sufferers is non-compliance with diet. The aim of this research is to determine the description of diet compliance in kidney failure patients at Guntur Garut Hospital. The research method used was descriptive, with a purposive sampling technique, the sample size was 25 respondents with the criteria being that the patient had undergone hemodialysis for more than 3 months and had no complications. The data collection technique was carried out using a questionnaire. The results of the study concluded that the majority of respondents (56%) did not comply with the diet. Suggestions from the results of research that have been carried out for health workers in the hemodialysis room at Guntur Hospital, especially nurses, to further improve education about the importance of diet for kidney failure patients.